From Anticipation to the Experience of Pain: The Importance of Visceral Versus Somatic Pain Modality in Neural and Behavioral Responses to Pain-Predictive Cues. Issue 9 (November 2018) - Koenen, Laura Ricarda; Icenhour, Adriane; Forkmann, Katarina; Theysohn, Nina; Forsting, Michael; Bingel, Ulrike; Elsenbruch, Sigrid
ABSTRACT: Objective: The aim of this study was to compare behavioral and neural anticipatory responses to cues predicting either somatic or visceral pain in an associative learning paradigm. Methods: Healthy women ( N = 22) underwent functional magnetic resonance imaging. During an acquisition phase, two different visual cues repeatedly signalled either experimental visceral or somatic pain. In a subsequent extinction phase, identical cues were presented without pain. Before and after each phase, cue valence and contingency awareness were assessed on visual analog scales. Results: Visceral compared to somatic pain–predictive cues were rated as more unpleasant after acquisition (visceral, 32.18 ± 13.03 mm; somatic, −18.36 ± 10.36 mm; p = .021) with similarly accurate cue-pain contingencies. After extinction, cue valence returned to baseline for both modalities (visceral, 1.55 ± 9.81 mm; somatic, −18.45 ± 7.12; p = .41). During acquisition, analyses of cue-induced neural responses revealed joint neural activation engaging areas associated with attention processing and cognitive control. Enhanced deactivation of posterior insula to visceral cues was observed, which correlated with enhanced responses within the salience network (anterior cingulate cortex, anterior insula) during visceral compared to somatic pain stimulation. During extinction, both pain modalities induced anticipatory neural activation in the extinction and salience network (all p FWE values < .05). Conclusions: Conditioned emotional responses to pain-predictive cues are modality specific and enhanced for the visceral modality, suggesting that pain anticipation is shaped by the salience of painful stimuli. Common but also modality-specific neural mechanisms are involved during cue-pain learning, whereas extinction of cued responses seems unaffected by modality. Future research should examine potential implications for the pathophysiology of chronic pain conditions, especially chronic visceral pain. Abstract : Supplemental digital content is available in the text.